INTERSPECIES CROSSES IN POTATO BREEDING IN UKRAINE - A. A. Podgayetsky (Вавиловский журнал генетики и селекции)
The potential of using wild potato species inbreeding and raise of donors of resistance to late blight and dry rot, the necessity of homozygotizationof alleles controlling valuable traits, possibility of raising primary and secondary interspecies hybrids, presence of efficient genes controlling the resistance to late blight and dry rot, and the possibility of introgressionof these genes to breeding material are considered. Varieties raised by backcrossing complex interspecies hybrids are characterized.